Studi Eksegesis Matius 22: 37 Tentang Makna Kasih Kepada Allah Dan Sesama Manusia Dan Impementasinya Bagi Kehidupan Masa Kini - Orpasanna, Adriel Nahason; Sahari, Gunar (Vieka Wahana Semesta, 2024)
Matthew 22:37 is the core of Jesus' teaching on love, outlining the two main commandments: love of God and love of neighbor. This is the first and greatest commandment.'” This verse emphasizes the two main interrelated commandments in Christianity: love of God and love of fellow human beings. This concept of love is not only the foundation of Christian law, but also reflects the deep and comprehensive relationship between humanity and God and neighbor. The purpose of this study is to explore the deep meaning of the commandment of love in its historical and theological context and the practice of the commandment in modern life today. The research methods in this paper include biblical text analysis, historical context, and theological analysis. The results show that the commandment of love remains a fundamental principle that remains relevant in today's social context. Applying Jesus' teaching on love can provide practical guidance for building harmonious and caring relationships in today's complex society. The conclusion emphasizes the importance of applying the principle of love in everyday life to build a more just and loving community in everyday life.